DESKRIPSI INDUSTRI PENGOLAHAN KELAPA SAWIT DI PT. TRI BAKTI SARIMAS PKS 2 IBUL, RIAU TAHUN 2020 - Dela Ristika Sari; Yulianti (JURNAL RISET INDRAGIRI, 2022)
Palm oil processing is one of the determining factors for the success of an oil palm plantation business. This study is aimed to examine the palm oil processing industry at PT. Tri Bakti Sarimas PKS 2 Ibul, Riau in 2020 where the subject of study is devoted to the palm oil processing system into CPO (Crude Palm Oil) and PKO (Palm Kernel Oil). The descriptive method is used in this study and data are taken through experiments, observation, interviews and documentation. The results showed that the processing of palm oil into CPO and PKO is processed to several stages and processes, namely weighing, grading and sorting, loading ramp, splitter, sterilizer, thresher, digester and press. PT. Tri Bakti Sarimas has carried out the processing of palm oil in accordance with standard operating procedure.